DIY (Do-It-Yourself) English Language Learning and Practice at Universitas Negeri Makassar - Nurfadhilah, Auliyanti Sahril; Basri, Muhammad; Nur, Sahril (Fakultas Sastra - Universitas Muslim Indonesia, 2023)
This phenomenological study explores the experiences, motivations, and challenges of students at Universitas Negeri Makassar engaging in DIY (Do-It-Yourself) English language learning and practice. The research aims to gain insights into self-directed language learning and provide valuable information for educational practices and policies in the university context. A purposeful sample of 15-20 students, representing a diverse range of experiences, was selected to participate in the study. Data collection involved a combination of semi-structured interviews, focus group discussions, and reflective journals, allowing for a comprehensive understanding of the students' perspectives. Inductive thematic analysis was employed to identify key themes and patterns in the data, with the findings presented as a rich, descriptive narrative. Strategies for establishing trustworthiness included triangulation of data sources, member checking, and peer debriefing. This study contributes to our understanding of DIY language learning by highlighting the DIY English language learning strategies, benefits and challenges, and students’ ways of assessing DIY English language learning at Universitas Negeri Makassar, ultimately informing future educational practices and policies.